Pengaruh Katalis Pelat Tembaga Untuk Mengurangi Emisi Karbon Monoksida (CO) dan Hidrokarbon (HC) Pada Kendaraan Roda Dua - Irzan Pujiriansyah; Samsul Hadi (Journal of Creative Student Research, 2024)
With increasing public awareness of environmental pollution, especially air pollution, especially CO and HC, the public's interest in reducing the rate of pollution is increasing. Therefore, the aim of this research is to find breakthroughs to help reduce air pollution by using cheap materials. This research is experimental research or experimental research. Research was carried out on trials of making a catalyst from copper material shaped like a wasp's nest. The copper plate is cut to size and folded like a wasp's nest. Data is taken from the nominal numbers printed on the Gas Analyzer monitor, by directly recording each engine rotation starting from idle, 1000, 2000, 2500 and 3500 rpm. The fuel used in this test uses pertalite and Pertamax as a comparison. The engine used has a capacity of 125cc. In this research, the material used was copper plate with a thickness of 0.9mm with a distance between fins of 4mm. The variations in catalytic length are 70mm, 90mm and 110mm. The catalytic shroud uses a standard 2009 Supra-X 125cc exhaust that has been modified internally to make room for the copper plate catalyst. The results taken from this research are the reduction in CO and HC levels in two-wheeled vehicles with an engine capacity of 125cc using a catalyst with a length of 110mm, where this reduction is 70% for CO and 24% for HC, respectively. Meanwhile, the lowest is using a catalyst with a length variation of 70mm with a yield of 8% for CO and 6% for HC.